INHIBITORY ACTIVITY OF ULIN BARK (Eusideroxylon zwageri) EXTRACT TO Lactobacillus acidophilus - Ina Rezki Rahmasari; I Wayan Arya Krishnawan Firdaus; Renie Kumala Dewi (FKG Unlam, 2021)
Background: Lactobacillus acidophilus is a bacterium which plays a role in dental caries. It is believed as a pioneering bacterium in advanced caries and much likely to be isolated in dentin caries zone, resulting in the needed for tooth restoration. The use of 2% Chlorhexidine digluconate as cavity cleanser is recommended as an effort to prevent seconday caries but can cause side effects. One of the natural materials that can be used as a cavity cleanser is ulin bark extract (Eusideroxylon zwageri), a traditional medicine originally from Kalimantan, because it contains phenolic, flavonoid, tannin, alkaloid, saponin and terpenoid. Purpose: To discover the inhibitory activity of ulin bark extract on Lactobacillus acidophilus growth. Methods: This was a true experimental laboratory and post test only with control group design, that used 20%, 40%, 60%, 80%, 100% concentrations of ulin bark extracts and K(+) 2% Chlorhexidine digluconate. Difussion method was used to test inhibitory activity with 6 treatment groups and 4 replications, comprising a total of 24 samples. All groups were incubated for 24 hours at 37ºC temperature. The inhibition zone was measured using calipers. Results: The 20%, 40%, 60%, 80% and 100% concentration of ulin bark extracts and 2% Chlorhexidine digluconate had an average inhibition zone of 7.17 mm, 9.02 mm, 11.14 mm, 13.06 mm, 15.17 mm and 19.22 mm. One Way ANOVA and Post Hoc Bonferroni tests showed significant difference between all groups. Conclusion: Ulin bark extract can inhibit Lactobacillus acidophilus growth starting from 20%, 40%, 60%, 80% and 100% concentration.